Let x 1 and x 2 denote the minimum value and the maximum value of x , respectively, satisfying ∣ x − 1 ∣ ≤ 2 .
If the area bounded between the curve x 2 − y 2 = 1 , x = x 1 and x = x 2 is of the form
A B − ln ∣ C + D E ∣ , where A , B , C , D , E are all positive integers with B , E square-free. Find A + B + C + D + E .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We note that the minimum and maximum values of ∣ x − 1 ∣ ≤ 2 occur at x 1 = 1 and x 2 = 3 respectively. The area required is given by the integral below:
I = 2 ∫ 1 3 x 2 − 1 d x = 2 ∫ 0 α sec u tan 2 u d u = 2 ∫ 0 α sec u ( sec 2 u − 1 ) d u = 2 ∫ 0 α sec 3 u d u − 2 ∫ 0 α sec u d u = 2 ( 2 sin u sec 2 u ∣ ∣ ∣ ∣ 0 α + 2 1 ∫ 0 α sec u d u ) − 2 ∫ 0 α sec u d u = 6 2 − ∫ 0 α sec u d u = 6 2 − ∫ 0 α tan u + sec u sec u tan u + sec 2 u d u = 6 2 − ln ( sec u + tan u ) ∣ ∣ ∣ ∣ 0 α = 6 2 − ln ( 3 + 2 2 ) Let x = sec u , d x = sec u tan u d u where α = sec − 1 3 Using reduction formula (see footnotes)
⟹ A + B + C + D + E = 6 + 2 + 3 + 2 + 2 = 1 5
Reduction formula: ∫ sec m x = m − 1 sin x sec m − 1 x + m − 1 m − 2 ∫ sec m − 2 x d x
Problem Loading...
Note Loading...
Set Loading...
∣ x − 1 ∣ ≤ 3 → − 1 ≤ x ≤ 3
x 2 − y 2 = 1 → y = ± x 2 − 1
Which is a symmetrical curve with respect to the x-axis. So, the area we're looking for is:
A = 2 ∫ 1 3 x 2 − 1 d x
x = cosh ( u ) → d x = sinh ( u ) d u
A = 2 ∫ 0 a c o s h ( 3 ) cosh ( u ) 2 − 1 sinh ( u ) d u
A = 2 ∫ 0 a c o s h ( 3 ) sinh 2 ( u ) d u
A = 2 ∫ 0 a c o s h ( 3 ) 2 cosh ( 2 u ) − 1 d u
A = 2 s i n h ( 2 u ) ∣ ∣ ∣ ∣ ∣ 0 a c o s h ( 3 ) − a c o s h ( 3 )
Now, to calculate a c o s h ( 3 ) :
u = a c o s h ( 3 ) → 2 e u + e − u = 3
Set e u = v
v + v 1 = 6 → v 2 − 6 v + 1 = 0 → v = 3 + 2 2 → a c o s h ( 3 ) = ln ( ∣ 3 + 2 2 ∣ )
Also, if e u = v , s i n h ( 2 u ) = v 2 − v 2 1 → s i n h ( 2 u ) = 1 2 2
So:
A = 6 2 + ln ( ∣ 3 + 2 2 ∣ )
Then:
a = 6 , b = 2 , c = 3 , d = 2 , e = 2 , a + b + c + d + e = 1 5